PEMERIKSAAN BAYI DAN PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI (MP ASI) DALAM UPAYA PENCEGAHAN STUNTING - Pratiwi Puji Lestari; Fika Aulia; Dwi Kartika Sari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
Globally in 2016, 22.9% or 154.8 million children under 5 years of age suffered from child stunting, which is defined by low height for age. Stunting is often not recognized by the public. Short stature is so common among people that it is considered normal. The difficulty in visually identifying stunted children and the lack of routine assessment of linear growth in primary health care services explain why it took so long to recognize the magnitude of this hidden scourge. The purpose of carrying out examinations for infants and toddlers and providing education about complementary foods is to screen for stunting and provide education about nutritious food. This Community Service activity is located in the working area of Sungai Tabuk III Health Center, precisely in Paku Alam Village. The activity of examining the growth and development of infants under five as well as education about the manufacture of complementary feeding for mothers of infants under five will be held on October 16, 2021. The target audience for this community service activity is infants aged 0 months to 5. The results obtained are that there are still children with stunting symptoms (below the red line and the z score in KMS -2) as well as increasing knowledge of targets that are known from evaluation through pretest and posttest.